2021
DOI: 10.1063/5.0071781
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation control using passive flow control techniques

Abstract: Passive flow control techniques, and particularly vortex generators have been used successfully in a broad range of aero-and hydrodynamics applications to alter the characteristics of boundary layer separation. This study aims to review how such techniques can mitigate the extent and impact of cavitation in incompressible flows. This review focuses first on vortex generators to characterize key physical principles. It then considers the complete range of passive flow control technologies, including surface con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 181 publications
0
10
0
Order By: Relevance
“…Besides, comparing the results with those from Churkin et al [11] obtained for similar flow conditions and wall morphology, the small-scale roughness is much more effective on the cylinder than on the NACA0015 hydrofoil due presumably to the significant surface curvature and faster separation of the boundary layer on the bluff body. Zaresharif et al [74] reported that the intensity of cavitation can be reduced with the aid of some laser-made textures as compared to polished surfaces. This is also consistent with our measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, comparing the results with those from Churkin et al [11] obtained for similar flow conditions and wall morphology, the small-scale roughness is much more effective on the cylinder than on the NACA0015 hydrofoil due presumably to the significant surface curvature and faster separation of the boundary layer on the bluff body. Zaresharif et al [74] reported that the intensity of cavitation can be reduced with the aid of some laser-made textures as compared to polished surfaces. This is also consistent with our measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Various passive methods of cavitation control based on these principles were discussed in detail in the review by Zaresharif et al [74] , including those employing the concept of variation of the contact angle. Numerous papers have been published so far, where the effect of wall irregularities on flow structure was investigated in detail for both a cylinder (e.g., [71] , [63] , [55] , [8] , [77] , [45] ) and other objects of different shapes (e.g., [53] , [39] , [7] , [33] , [11] , [34] ).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that here the bubble formation due to the pressure reduction is different from cavitation, which happens when the local pressure of the liquid falls below its saturated vapor pressure. 37,38 For flowing water at 20 °C, cavitation bubbles typically generate when the local pressure falls below its vapor pressure of ∼2.73 kPa, which indicates that a severe pressure reduction of ∼100 kPa is needed to induce cavitation. However, in this experiment, bubbles are formed when the local pressure reduction in the crevice is less than 1 kPa, which is much too small to induce cavitation.…”
Section: Observations Of Bubble Growth and Drag Reductionmentioning
confidence: 99%
“…Podnar et al [20] studied the influence of spherical blade shape on flow characteristics, and found that modifying the design parameters of hydrofoil can reduce the occurrence and development of cavitation. In addition, setting surface roughness [21] , [22] , [23] , vortex generators [24] , [25] , [26] and jet holes [27] can also realize the passive control of hydrofoil cavitation. It was found that the passive control methods of cavitation have a low cost, easy operation, high flexibility, and good development prospects.…”
Section: Introductionmentioning
confidence: 99%